Differential Roles for Diploid and Polyploid Hepatocytes in Acute and Chronic Liver Injury - Wilkinson, Patrick D; Duncan, Andrew W (Seminars in liver disease, 2021)
Hepatocytes are the primary functional cells of the liver that perform essential roles in homeostasis, regeneration, and injury. Most mammalian somatic cells are diploid and contain pairs of each chromosome, but there are also polyploid cells containing additional sets of chromosomes. Hepatocytes are among the best described polyploid cells, with polyploids comprising more than 25 and 90% of the hepatocyte population in humans and mice, respectively. Cellular and molecular mechanisms that regulate hepatic polyploidy have been uncovered, and in recent years, diploid and polyploid hepatocytes have been shown to perform specialized functions. Diploid hepatocytes accelerate liver regeneration induced by resection and may accelerate compensatory regeneration after acute injury. Polyploid hepatocytes protect the liver from tumor initiation in hepatocellular carcinoma and promote adaptation to tyrosinemia-induced chronic injury. This review describes how ploidy variations influence cellular activity and presents a model for context-specific functions for diploid and polyploid hepatocytes.